Alone but better off? Adult child migration and health of elderly parents in Moldova - Marcus Böhme; Ruth Persian; Tobias Stöhr (Kiel Institute for the World Economy (IfW), 2013)
Increasing labor migration and simultaneous aging of societies are two important demographic developments many poor countries face. Elderly people who are left behind may experience a decrease in welfare when their children migrate. This paper investigates the e ect of migration on various dimensions of elderly health using unique data from Moldova, which has one of the highest emigration rates in the world. We nd positive migration e ects on the body mass index (BMI), mobility and self-reported health. No e ects are found on depression and cognitive capacity. We trace these positive outcomes to an income e ect which leads to improvements in diet and a reallocation of time use from subsistence farming to leisure and sleep. These positive e ects seem to compensate the elderly for decreasing social contact with their migrant family members.
Keywords: F22; I12; I15; J14; O15; 330; international migration; elderly health